PHYTOCHEMICAL SCREENING, HPTLC AND GC-MS PROFILING IN THE RHIZOMES OF ZINGIBER NIMMONII (J. GRAHAM) DALZELL - FINOSE, ASSAMAKANTAKATH; GOPALAKRISHNAN, VELLIYUR KANNIAPPAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: The preliminary phytochemical screening was carried out in the hexane and methanolic extracts of Z.nimmonii rhizomes. HPTLC and GCMS profiling were done to develop the fingerprint of the plant to detect the major chemical constituents of the plant. Methods: Preliminary screening involved the qualitative methods to detect the presence of carbohydrates, flavonoids, alkaloids, terpenoids, tannins, oils and fats. HPTLC fingerprint was developed for the hexane extract using hexane, ethyl acetate and isopropanol as the solvent system in the ratio 7:2:1.GCMS profiling was done using triple axis detector. Results: The study revealed the presence of flavonoids, oils and fats as the major components. Terpenoids and tannins were present in moderate amounts. HPTLC profiling revealed 6 peaks in 254nm wavelength and 2 peaks in 366nm.GCMS profiling of the hexane extract gave the presence of 23 components with benzoic acid(35%),3,5-dicyclohexyl-4-hydroxy-,methyl ester and 1-chloroeicosane(29%) as the major components. Conclusion: Z.nimmonii contains many important components which has significant role in the drug research and isolation of the compounds will be of therapeutic usage. Keywords: Z.nimmonii. phytochemical screening, HPTLC, GCMS, therapeutic.